Evidências da subalternização das autoras negras no livro didático: uma proposta de construção da afropotência no espaço escolar - Santana, Kátia Cilene Souza Alcântara (2023)
The Law 10.639/2003 ensures the inclusion in Basic Education of the history of Africa and the African, the struggle of Black people in Brazil, their culture, and the importance of Black individuals in the formation of Brazilian society. It aims to reclaim the contributions of the Black population to the economy, politics, culture, and other social areas, strengthening the effective implementation and respect for cultural and ethnic-racial diversity. However, for this law to be sanctioned, it required significant struggle and resistance from Brazilian Black Movements. The Professional Master's Degree Profletras guided us to ponder how this law is being put into practice in our country, which has deep colonial and patriarchal roots. It's noticeable that the literature chosen as canonical is predominantly authored by white men and women. From this reflection, we researched whether the voices of Black female writers were being silenced in the textbook chosen by teachers in the municipal network of Catu-Ba for 9thgrade students in Elementary School. After evaluating the Geração Alpha textbook from the 9th grade by the SM publisher and noting the invisibility of Black female writers, our objective was to introduce students to texts authored by Black women, aiming to develop their "afropotência" (a term related to African empowerment). To achieve our goals, we constructed the "Afropotência das Yabás Trail: Weaving Words of Resistance and Afroempowerment through the Perspectives of Black Female Writers." This trail is based on the voices of Black female writers, the power of language, and orality. For the development of this research, this work is grounded in González (2020), Kilomba (2020) e bell hooks (2017). In this way, we ensure compliance with Law 10.639, shattering chains that marginalize Black female writers in classrooms, and fostering "afropotência" within the school space.